GROWTH AND YIELD PERFORMANCE OF RICE (ORYZA SATIVA VAR. NSIC RC222) AS INFLUENCED BY VARYING LEVELS OF NITROGEN FERTILIZER - Tangpos, Marciano D (Journal of Agriculture and Technology Management, 2022)
The appropriate nitrogen fertilizer application rate assures optimum net returns in rice production. Thus, this study was conducted to a.) evaluate the growth and yield performance of NSIC Rc222; b.) identify the best nitrogen fertilizer level, and c.) evaluate the profitability of NSIC Rc222 at different levels of nitrogen fertilizer. Field experiments were conducted during the dry season from January 31 to May 5, 2020. The area was laid out in Randomized Complete Block Design (RCBD) with three replications. Five nitrogen levels (0,150,120,100 and 75 kg N/ha) were designated as the treatments. Results showed that applying fertilizer at the rate of 75-60-60 NP205K2O significantly headed and matured earlier at 81.67 and 101 days after planting and grew at 89.10 cm tall but was comparable to other treatments, excluding no fertilizer application. Likewise, fertilizer application at 120-60-60 NP205K2O significantly increased its productive tillers, panicle length, percent filled spikelets, the weight of grains per hill, weight of 1000 grains, and lower unfilled spikelets. Further, the use of 120-60-60 NP205K20 produces a higher grain yield at 4.39 t/ha and has a net income of PHP 82,880, followed by 100, 75, 150 kg/ha, and 0 nitrogen with corresponding net income values of 72,895, 66,320, 54,070, and 26,900 pesos per hectare, respectively.